Overview on inhalable nanocarriers for respiratory immunization - Ferreira, Rui C. (2020)
Despite the value of vaccination, the control of re-emerging infectious and non-infectious diseases remains a challenge for researchers. In this topic, mucosal immunization, in particular at airway mucosa, is receiving increased investigational focus. Innovative vaccine platforms to deliver immunogens with or without adjuvants in a safe and stable manner have been explored to improve vaccine efficacy and induce long-term and protective immunity. This review provides an overview of the features of respiratory immunization and the fate of inhalable nanocarriers in the respiratory tract. The review also highlights the most representative delivery approaches based on inhalable nanocarriers, including polymeric, lipid and inorganic-based nanosystems, which can enhance vaccine uptake by antigen-presenting cells. The review takes into consideration the most relevant and recent in vivo studies to provide readers a realistic insight into the potential of these technologies in the advantages and potential hurdles to clinical and commercial success of these platforms for vaccination.